New Technologies, Multiple Literacies and Teaching English as a Foreign Language - Cardoso, Silene (2018)
This article presents and briefly discusses the results from a survey conducted with English teachers of the third cycle and secondary education in Portugal as part of a study on multiple literacies and Web 2.0 in English as a foreign language (EFL) classroom (Cardoso). Based on the answers provided, it can be assumed that among this group of teachers, new technologies tend to be part of their professional practice. However, it is unclear if digital tools have been used to actually promote more innovative ways of teaching or just as a different way to approach more traditional methods. Moreover, it seems that suitable guidance, training and further development of appropriate materials are required to facilitate and better integrate new technologies in the EFL classroom